Analysis of the Differences in OCOP Products between Thanh Hoa Province and Nghe an Province - Nguyễn Thị Mai (Journal La Bisecoman, 2021)
This research analyzes the differences in OCOP products between Thanh Hoa province and Nghe An province, Vietnam. OCOP products are analyzed based on three aspects: Product mean score (Product level), Structure of product type, and Structure of product region. The analysis sample includes 115 OCOP products from 3 to 5 stars in each province (230 products in total). Research results are confirmed that there are some differences in OCOP Products between Thanh Hoa province and Nghe An Province. Whereby, there is the difference in the mean score, the difference in the structure of product type, and the difference in the structure of product region. These results help the authorities in both provinces to have appropriate policies and support tools to develop local OCOP products by the goals and orientations of each locality to commercialize strongly rural products that have their comparative advantage.